Investigating the urban heat island effect of transit oriented development in Brisbane - Kamruzzaman, Md; Deilami, Kaveh; Yigitcanlar, Tan (Journal of transport geography, 2018)
Transit oriented development (TOD) has been identified as a key planning tool to limit sprawl development and thereby to tackle a range of undesirable outcomes of cities. Generally, research findings are supportive of TOD policies over sprawl development in many aspects such as reducing car-dependency, congestion, and emissions. Although sprawl development has been identified as a key factor of the urban heat island (UHI) effect, a phenomenon when an urban area experiences a higher temperature compared to its surrounding non-urban areas, existing empirical studies, however, lack to answer whether TODs are likely to reduce the UHI effect. Using Brisbane as a case, this research answers this question by: a) identifying TOD neighbourhoods based on a cluster analysis of six built environment factors (residential density, employment density, land use diversity, intersection and cul-de-sac densities, public transport accessibility levels); b) validating the selection of TOD neighbourhoods based on travel behaviour analysis of residents living between TOD and non-TOD areas; c) examining patterns of UHI effects between the areas and their changes over the period of 2004–2013 based on Landsat remote sensing data; and d) identifying the factors contributing to the UHI effects in TODs. Results show that TODs experienced a higher level of UHI effect compared to non-TOD areas. Although both areas experienced an increase in the UHI effect between the periods, the rate of increase was found to be significantly higher in TOD areas. Land use diversity, percentage of porous land vis-à-vis density significantly contributed to the UHI effect. The findings suggest that a compromise between natural and built-up areas is essential to reduce the UHI effect while contributing to the ultimate goal of TODs – i.e. to create settings which prompt people to drive less and ride public transit more.